I am asking that whether we should consider that a person has sent a mail to himself or not
Two possible answers :
1. ∃x∀y[(x≠y)→M(x,y)] :- In this ,it will be true even when x=x,as implication becomes true,So there exits a student who has sent a mail to everone(including himself)
2. ∃x∀y[(x≠y)^M(x,y)]:-This means there is a student who has sent a mail to everyone except himself.
Nowthe only difference is 1. answer allowing x=x,where as second is not.
But what actually is implied by the question i am not getting